Enhanced disengagement of auditory attention and phonological skills in action video gamers. (October 2022) - Mancarella, M.; Antzaka, A.; Bertoni, S.; Facoetti, A.; Lallier, M.
Abstract: Video games play a major role in the everyday life of children, teenagers, and adults. Several studies show that action video games (AVGs) improve visual attentional efficiency. AVGs also appear to improve reading speed and phonological skills in children with developmental dyslexia. These results have been linked to the intrinsic characteristics of AVGs, in which fast disengagement of multisensory attention allows for efficient extraction of relevant dynamic information, a skill that is crucially also involved in phonological and reading skills. We tested the hypothesis that AVG players demonstrate faster auditory attention disengagement in an auditory spatial cuing task, as well as better phonological and reading performance than non-players. We found that AVG players were faster in spatial localization of auditory targets and showed enhanced attentional disengagement as indexed by a smaller cuing effect. AVG players also showed better phonological decoding and working memory skills. Moreover, the beneficial effects of AVGs, as measured by faster attentional disengagement, were linked to better phonological and reading skills in adult AVG players. We suggest that a more efficient attentional disengagement - controlled by the posterior parietal cortex - induces enhanced multisensory processing in AVG players. Highlights: Auditory attentional skills are boosted in action video games players. Auditory attention is correlated to better phonological and reading skills. Action video games may be related to a boost not only in visual, but also in auditory attention. Multisensory advantages from action video games might transfer to the reading domain.